2009
DOI: 10.1016/j.ijhydene.2009.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Carbon supported nano-sized Pt–Pd and Pt–Co electrocatalysts for proton exchange membrane fuel cells

Abstract: Nano-sized Pt-Pd/C and Pt-Co/C electrocatalysts have been synthesized and characterized by an alcohol-reduction process using ethylene glycol as the solvent and Vulcan XC-72R as the supporting material. While the Pt-Pd/C electrodes were compared with Pt/C (20 wt.% E-TEK) in terms of electrocatalytic activity towards oxidation of H 2 , CO and H 2-CO mixtures, the Pt-Co/C electrodes were evaluated towards oxygen reduction reaction (ORR) and compared with Pt/C (20 wt.% E-TEK) and Pt-Co/C (20 wt.% E-TEK) and Pt/C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…At present, to design and fabricate highly active Pt-based alloy electrocatalysts has been an important strategy by means of engineering the alloy composition, structure size, and morphology etc [6]. For instance, a variety of Pt alloy nanomaterials has been developed to enhance its MOR activity considering the alloy effect, such as PtCu nanoparticles [7], PtRu nanotubes [8], supported PtRu nanoparticles [9e11], PtAu [12] and PtPd [13] nanoparticles and so on. Recently, non-precious 3d transition metals (referring to the unfilled subshell electrons in the 3d-orbital), such as Fe, Co, and Ni, were found to have great synergistic catalytic effect on the MOR activity of Pt [13e16] besides their remarkably synergistic role on oxygen reduction reaction (ORR) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, to design and fabricate highly active Pt-based alloy electrocatalysts has been an important strategy by means of engineering the alloy composition, structure size, and morphology etc [6]. For instance, a variety of Pt alloy nanomaterials has been developed to enhance its MOR activity considering the alloy effect, such as PtCu nanoparticles [7], PtRu nanotubes [8], supported PtRu nanoparticles [9e11], PtAu [12] and PtPd [13] nanoparticles and so on. Recently, non-precious 3d transition metals (referring to the unfilled subshell electrons in the 3d-orbital), such as Fe, Co, and Ni, were found to have great synergistic catalytic effect on the MOR activity of Pt [13e16] besides their remarkably synergistic role on oxygen reduction reaction (ORR) [5].…”
Section: Introductionmentioning
confidence: 99%
“…With the advantages of the activity enhancement and the cost reduction by alloying with the 3d metal, the morphology of these alloy nanomaterials has also attracted great attention by virtue of the structure effect [6]. Some PtCo and PtNi alloy nanostructures, such as carbon supported nanoparticles [13,15,17] and hollow nanospheres [16], have been prepared with the improvement of MOR activity on Pt. Despite the increasing attention on the methanol electrooxidation on Pt-3d metal alloy nanomaterials, investigations on the structure stability of these nanocatalysts and the physically catalytic effect of 3d metals on Pt are relatively lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks of the TiO 2 anatase phase occurred at 26°, 34°, and 52° [29,30]. The peaks at 27.3°, 35.9°, and 43.9° were ascribed to the (110), (101), and (111) planes of TiO 2 rutile, respectively [18]; compared with pure TiO 2 , a new peak was observed between 43° and 45°. Huang et al [30] found that the difference between doped TiO 2 /CNTs (700 °C) and pure TiO 2 is the appearance of new peaks between 43° and 45°.…”
Section: Methodsmentioning
confidence: 93%
“…Nanomaterials and mesoporous materials have attracted enormous attention essentially due to their wide range of application areas, including sensor [10][11][12][13], supercapacitor [14], biosensor [15][16][17], and GDE [18]. The Pt-based nanocatalyst usually was used in acid solution.…”
mentioning
confidence: 99%
“…9). PdOePt structure exhibit electron exchange and transfer ability [15,18,19]. Hence, Reaction (4) proceeds more easily when loading PdO and Pt nanoparticles than when loading only Pt or PdO, explaining the increased hydrogen gas yield attained when both PdO and Pt nanoparticles were used.…”
Section: Effect Of Bimetallic Pdeptmentioning
confidence: 99%